Assessment of Effect of TENS, EMS, Active and Passive Exercises in Chronic Hemiplegic Stroke Patients Using Modified Ashworth Scale - Shilpa Hardaha; Anu Jain; Sumer Singh; Tapasya Tomar; Deepika Bakshi (Asian Journal of Medical Research, 2022)
Background: The aim is to assess effect of TENS, EMS, active and passive exercises in chronic hemiplegic stroke patients using Modified Ashworth Scale. Subjects and Methods: All were divided into 4 groups of 20 each. Group A hemiplegic subjects were given TENS, group B hemiplegic subjects were given EMS, group C hemiplegic participants were subjected to active and passive exercise and group D hemiplegic participants were subjected to active and passive exercise along with TENS and EMS. Spasticity was calculated by the MAS. The Timed Up and Go (TUG) test was used to evaluate dynamic balance. Results: The mean pre- treatment FMA value in group A was 26.5 and post- treatment FMA was 41.7, in group B pre- treatment FMA value was 26.8 and post- treatment FMA value was 42.2, in group C pre- treatment FMA value was 26.8 and post- treatment FMA value was 43.8 and in group D pre- treatment FMA value was 26.9 and post- treatment FMA value was 45.1. The mean pre- treatment NDS value in group A was 25.6 and post- treatment NDS was 18.4, in group B pre- treatment NDS value was 25.8 and post- treatment NDS value was 20.7, in group C pre- treatment NDS value was 25.4 and post- treatment NDS value was 17.3 and in group D pre- treatment NDS value was 25.8 and post- treatment NDS value was 15.2. The mean pre- treatment MAS value in group A was 2.67 and post- treatment MAS was 2.04, in group B pre- treatment MAS value was 2.80 and post- treatment MAS value was 2.70, in group C pre- treatment MAS value was 2.82 and post- treatment MAS value was 1.98 and in group D pre- treatment MAS value was 2.67 and post- treatment MAS value was 1.82. The mean pre- treatment TUG value in group A was 26.1 and post- treatment TUG was 21.4, in group B pre- treatment TUG value was 25.4 and post- treatment TUG value was 22.8, in group C pre- treatment TUG value was 26.8 and post- treatment TUG value was 25.8 and in group D pre- treatment TUG value was 26.6 and post- treatment TUG value was 20.2. Conclusion: Physiotherapy is one of effective management in retaining strength, spasticity and range of movement in post stroke patients. Early rehabilitation such as TENS, EMS and active and passive exercise, in patients with acute CVA, body balance and movement coordination training can help them improve their ability to move their hemiplegic lower extremity.